Muscular effort increases hand-blink reflex magnitude. (29th May 2019) - Bufacchi, R.J.; Ponticelli, S.; Novembre, G.; Kilintari, M.; Guo, Y.; Iannetti, G.D.
Highlights: The magnitude of hand-blink reflex is increased by tonic cortico-spinal activation. This effect is smaller than the commonly observed HBR increase when the stimulated hand is near the eye. Nonetheless, when using HBR as an indicator of behavioural relevance, this effect should be taken into account. Abstract: Defensive motor responses elicited by sudden environmental stimuli are finely modulated by their behavioural relevance to maximise the organism's survival. One such response, the blink reflex evoked by intense electrical stimulation of the median nerve (Hand-Blink Reflex; HBR), has been extensively used to derive fine-grained maps of defensive peripersonal space. However, as other subcortical reflexes, the HBR might also be modulated by lower-level factors that do not bear direct relevance to the defensive value of blinking, thus posing methodological and interpretive problems. Here, we tested whether HBR magnitude is affected by the muscular effort present when holding the hand in certain postures. We found that HBR magnitude increases with muscular effort, an effect most likely mediated by the increased corticospinal drive. However, we found strong evidence that this effect is substantially smaller than the well-known effect of eye-hand proximity on HBR magnitude. Nonetheless, care should be taken in future experiments to avoid erroneous interpretations of the effects of muscular effort as indicators of behaviour relevance.